Johnny, Alpen a Fi - Llewelyn, Dafydd (Gwasg Carreg Gwalch, 2020)
Owen's life is fine: as a television producer with an independent company in the capital, he has been milking the system for years, earning lots of money for only a little work. But things change when his wife leaves him... and he is sacked.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books